ARAHAN PENGEMBANGAN PEMBELAJARAN GEOGRAFI BERBASIS KULIAH KERJA LAPANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN GEOGRAFI STKIP PESISIR SELATAN - alexander Syam (STKIP Pesisir Selatan, 2017)
Abstract: Geography teaching essentially develops students' ability to recognize and understand natural phenomena in relation to spatial and territorial. When learning georafi students sometimes feel bored and lazy to learn the theory because it is considered difficult and difficult to understand so participate in Field Work Lecture (KKL). Field Work Lectures function applying theory in the classroom with in the field so it will affect the learning achievement and effectiveness of learning. The method used is qualitative method. The subjects of this study are students who will conduct workshops lapanga on cartography courses, cartographic pratik, remote sensing and interpretation of aerial photography. Data analysis begins with an interview to the subject of research on Field Work Lecture, while for the interest of learning data used tabulation then depicted in graph. Referral The development of learning field work field in education majors Geography Education Geography STKIP Pesisir Selatan is in accordance with field teaching approaches field work put forward by Rice and Bullman. Implementation of Field Work Lectures in Geography Education STKIP Pesisir Selatan consists of preparatory, implementation, and post-field work. Field work lectures are also able to increase student interest in geography learning and some development for field college learning so that students' interest in learning and willingness is higher among them 1) Location compatibility with KKL themes 2) Present prominent symptoms 3) Locations easy to reach 4) Safe to be visited 5) Relatively low cost to come 6) Availability of preliminary data about the location 7) Composition of clear committee and event Keywords: fieldwork, development direction, interest in learning